2009
DOI: 10.1177/0093854809340991
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reoffense Risk in Adolescents Who Have Committed Sexual Offenses

Abstract: Clinicians are often asked to assess the likelihood that an adolescent who has committed a sexual offense will reoffend. However, there is limited research on the predictive validity of available assessment tools. To help address this gap, this study examined the ability of the Estimate of Risk of Adolescent Sexual Offense Recidivism (ERASOR), the Youth Level of Service/Case Management Inventory (YLS/CMI), the Psychopathy Checklist: Youth Version (PCL:YV), and the Static-99 to predict reoffending in a sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 67 publications
6
36
2
1
Order By: Relevance
“…Further, we found that the predictive value of the total RISc score corresponded with a high effect size for predicting nonviolent recidivism (AUC = .723), with a medium effect size for predicting nonviolent recidivism (AUC = .704), and with a small effect size for predicting sexual recidivism (.585) (given the criteria of Rice & Harris, 2005). Previous research also showed that risk assessment instruments for general recidivism are only weak predictors for sexual recidivism (e.g., Schmidt et al, 2011;Seto & Lalumière, 2010;Viljoen, 2009). A specific risk assessment instrument seems to be needed for predicting sexual reoffending to an acceptable degree, in which specific risk factors, such as deviant sexual interests, prior sexual offenses, and deviant victim choices are assessed (Hanson & Bussiere, 1998;Hanson & Morton-Bourgon, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Further, we found that the predictive value of the total RISc score corresponded with a high effect size for predicting nonviolent recidivism (AUC = .723), with a medium effect size for predicting nonviolent recidivism (AUC = .704), and with a small effect size for predicting sexual recidivism (.585) (given the criteria of Rice & Harris, 2005). Previous research also showed that risk assessment instruments for general recidivism are only weak predictors for sexual recidivism (e.g., Schmidt et al, 2011;Seto & Lalumière, 2010;Viljoen, 2009). A specific risk assessment instrument seems to be needed for predicting sexual reoffending to an acceptable degree, in which specific risk factors, such as deviant sexual interests, prior sexual offenses, and deviant victim choices are assessed (Hanson & Bussiere, 1998;Hanson & Morton-Bourgon, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the individual items, the total group of minors obtained higher scores on the following: Poor School Achievement and Low Interest/Commitment to School or Work (Viljoen et al, 2009; Weerman, 2010; Van der Put, 2011; Cuervo and Villanueva, 2015; Harder et al, 2015), Peer Delinquency (Fergusson et al, 2007; Van der Put, 2011; Cuervo and Villanueva, 2015; Harder et al, 2015; Ortega-Campos et al, 2016; Makarios et al, forthcoming) and Poor Parental Management (Chambers et al, 2001; Álvarez-García et al, 2016; Ortega-Campos et al, 2016; Makarios et al, forthcoming). The lowest mean score in the group of protective factors was for Resilient Personality Traits (Mowder et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, interventions from Juvenile Justice should address the criminogenic needs that the juvenile presents, in order for the intervention and the youth’s experience with Juvenile Justice to be as effective as possible, and to meet the objective of reducing the effect and presence of risk factors in the repeat offenders (Andrews and Bonta, 2010; Polaschek, 2012; Childs et al, 2014; Ortega-Campos et al, 2016). The SAVRY proves to be a good instrument for younger offenders, discriminating level of risk and risk factors between recidivist and non-recidivist (McEachran, 2001; Catchpole and Gretton, 2003; Gammelgard et al, 2008; Schwalbe, 2008; Welsh et al, 2008; Viljoen et al, 2009; Vincent et al, 2011; Hilterman et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations